Network Feminist Actions: Analysis of the Hashtag #March8M in Mexico - Olmedo Neri, Raul Anthony (2020)
This paper analyzes the generated network around hashtag #Marcha8M in Mexico by means of the social network analysis method (SNA) and three indicators of this method. NodeXL software was used to obtain the information generated between March 4 and 9, 2020, and thus visualize the network. With this study, it is possible to analyse a way in which social movements appropriate social media and link with areas from communication’s field.